NARRATIVAS AUDIOVISUAIS NO PIAUI: Cultura e Sociedade na Linguagem do Cinema Universidade Metodista de São Paulo Programa de Pós-Graduação em Comunicação Social São Bernardo - Rocha, Rosa Edite da Silveira (2011)
This study suggests a research on the audio-visual production from Piauí, aiming to understand how the cultural matters and the narratives singularities presented during the historical development of the visual culture from Piauí are dealt. Therefore, the discursive, imagistic and technological matters addressing cultural realities that influenced the Brazilian avant-garde cinema, i.e. Cinema Novo and Cinema Marginal, were analyzed. The sources for this research are Super-8 mm Film productions shot from 1972 to the mid 1985‟s, when a second cinematographic cycle comes to an end. This qualitative study uses bibliographical and documental researches, supported by interviews and document analysis from that time to study the audiovisual productions. Piauí‟s social, political, technological and economic matters were taken in account when those videos where made. It is concluded that cultural practices and technological resources are a visual culture that represents the local anxieties and criticisms and reflects the characterization of the people from Piauí.